2022
DOI: 10.3390/biom12101498
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Peritoneal Mesothelial Cells in Peritoneal Adhesion

Abstract: A peritoneal adhesion (PA) is a fibrotic tissue connecting the abdominal or visceral organs to the peritoneum. The formation of PAs can induce a variety of clinical diseases. However, there is currently no effective strategy for the prevention and treatment of PAs. Damage to peritoneal mesothelial cells (PMCs) is believed to cause PAs by promoting inflammation, fibrin deposition, and fibrosis formation. In the early stages of PA formation, PMCs undergo mesothelial–mesenchymal transition and have the ability to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 133 publications
0
30
0
Order By: Relevance
“…Prevention of fibrin and fibroblasts from accumulating on the injured peritoneum is critical to avoid postoperative adhesions. , The antifouling properties of the HD hydrogel were investigated. Our in vitro study indicated that only a few proteins adhered to the HD hydrogel surface in a bovine serum albumin (BSA) solution, which were significantly lower compared to tissue culture polystyrene surface (TCPS) (Figure a).…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prevention of fibrin and fibroblasts from accumulating on the injured peritoneum is critical to avoid postoperative adhesions. , The antifouling properties of the HD hydrogel were investigated. Our in vitro study indicated that only a few proteins adhered to the HD hydrogel surface in a bovine serum albumin (BSA) solution, which were significantly lower compared to tissue culture polystyrene surface (TCPS) (Figure a).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Peritoneal adhesion development is related to a variety of mechanisms, including inflammation, collagen deposition, wound healing, and angiogenesis. ,, Most barrier materials for preventing peritoneal adhesion primarily aim to reduce the formation of adhesive bands but often overlook their regulatory role in inflammation, fibrinolysis, and related cytokines during adhesion formation . To explore the inhibitory effects of the HD hydrogel on inflammation, we determined the concentrations of TNF-α and IL-6 in serum using an enzyme-linked immunosorbent assay (ELISA) (Figure a,b).…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 6 ] Stimulation from surgical injury will further aggravate inflammatory responses and fibrinolytic imbalance, leading to the development of more severe adhesions. [ 24a,25 ] An enzyme‐linked immunosorbent assay was performed to determine whether the ODE–ME hydrogel could alleviate chronic inflammation and fibrinolytic imbalance in mice with MetS after surgery. Compared with the NCD + Model group, serum IL‐6, IL‐1β, TNF‐α, and plasminogen activator inhibitor‐1 (PAI‐1) levels were higher in the HFD + Model group; however, tissue‐type plasminogen activator (t‐PA) levels were lower; this suggests that mice with MetS have more severe postoperative inflammation and lower fibrinolytic activity, which are closely associated with adhesion severity (Figure 8D,E).…”
Section: Resultsmentioning
confidence: 99%
“…Adhesion may occur following chronic peritoneal inflammation, peritoneal dialysis, and endometriosis. 1 Adhesions are a common complication of surgery, occurring in up to 50%-95% of people who undergo abdominal or pelvic surgery, and place a tremen dous clinical and financial burden on public health. 2 Adhesion formation causes a range of symptoms like chronic pain, bowel obstruction, urinary dysfunction, and female infertility.…”
Section: Introductionmentioning
confidence: 99%